Optimising Asthma Self-Management: Preliminary Validation of an Arabic Version of the Inhaler Technique Questionnaire - Malath Al-Juhaishi; Chiao Xin Lim; Ieva Stupans; Wejdan Shahin; Thilini R. Thrimawithana; Vincent Chan (Pharmacy)
Background: Correct inhaler technique is vital for managing respiratory conditions like asthma. Patients from culturally and linguistically diverse backgrounds are at higher risk of sub-optimal adherence and errors in inhaler technique. This study aimed to validate an Arabic version of the inhaler technique questionnaire for self-assessment of the metered-dose inhaler (MDI) technique by assessing agreement between observed and self-reported techniques among Arabic-speaking individuals with asthma in Australia. Methods: Observational assessments of 30 participants using an MDI, followed by completion of the translated inhaler technique questionnaire by the same participants. The questionnaire comprised nine questions pertaining to the inhaler technique. The level of agreement between the observed and self-reported technique for each of the nine MDI technique steps was subsequently determined using intraclass correlation. Results: The majority of participants were women, aged 25–44 years (70%). An overall Kappa score of 0.768 indicated good agreement between observed and self-reported datasets, with stepwise agreement ranging from 52.4–100%. Steps involving taking a big breath before inhaler use (step 2) and exhaling slowly (step 8) were the least well correlated. Conclusions: The preliminary validated MDI inhaler technique questionnaire may be used as a self-assessment tool by Arabic speakers, aiding healthcare professionals, and empowering individuals living with asthma to self-manage their condition.